185k views
4 votes
Find the inverse of f(x)=2x+1

User Mpavlov
by
5.6k points

2 Answers

6 votes

Answer:


h(x) = (x-1)/(2)

Explanation:

The inverse function is the function which when plugged in to the original one yields the argument (x).

Knowing this we do the following, let h(x) be the inverse function of f:


f(x)=2x+1 \ \ \ \ f(h(x)) = 2(h(x)) + 1 = x\\h(x) = (x-1)/(2)\\Now \ we \ verify \ if \ it \ yields \ x.\\f(h(x)) = f((x-1)/(2)) = 2((x-1)/(2)) + 1 = x -1 + 1 = x\\Thus \ h(x) \ is \ the \ inverse\ function \ of \ f

User Daniel Brady
by
6.0k points
4 votes

Answer:

y=0.5(x-1)

Explanation:

To find the inverse of a function, you have to substitute yfor x in the equation and simplify to get a normal equation again. In this case, f(x) is y.

y=2x+1

x=2y+1

2y+1=x

2y=x−1

y=0.5(x−1)

So there you have it.

User Dhara
by
5.7k points